Work-At-Home and the Quality of Working Life - Shamir, Boas; Salomon, Ilan (Academy of Management Review, 1985)
Innovations in telecommunications technology increase the possibilities of working from the home. Implications of work-at-home arrangements for the individual's quality of working life are discussed. Included are discussions of several major aspects of the work experience relevant to quality of working life, analyses of the differences along these aspects between working at home and working at a normal workplace, and speculation about the possible consequences for the individual of the transfer of jobs from employers” premises to employees' homes.